ENHANCING INTERCULTURAL COMPETENCE IN UKRAINIAN HIGHER EDUCATION: A COMPARATIVE ANALYSIS OF VIRTUAL EXCHANGE AND COLLABORATIVE ONLINE INTERNATIONAL LEARNING IN EUROPE, THE USA, AND CANADA - Lavrysh, Yuliana; Lukianenko, Valentyna (Studies in Comparative Education, 2024)
Giving more and more attention to fostering multi-disciplinary and cross-cultural competences has become inevitable in today's interconnected world for future generations. Virtual exchange and collaborative online international learning programs provide invaluable opportunities for meaningful and intellectually stimulating interactions with people from different corners of the world, and thereby improve global competence. This study looks into the case where both cases were introduced into the Ukrainian educational space. The VE programs not only extend the language comprehension and communication skills, but respond to the development of empathy, collaboration and problem-solving skills. Notwithstanding obstacles, for instance, arousing students’ involvement and low level of institutional support. However, VE and COIL programs would vastly increase the cross-bordering of Ukrainian universities. This article shows that the creation of a national educational center for the training of professionals, the spread of the advantages of digitization and the blending of education with the virtual environment need special attention. The supportive initiatives through these innovative ways, Ukrainian higher education can make the students ready for success in the multifaceted world, which brings peace and a sustainable future.